Gestión administrativa y calidad del servicio en la Institución Prestadora de Servicio de Salud 1 – 3 América, 2023 - Reategui Suncion, Victor Adrian (2023)
This research was carried out with the purpose of determining the relationship between administrative management and quality of service in the Health Service Provider Institution 1 – 3 América, 2023. The approach used in the study was applied, descriptive-correlational and with a non-experimental design. The sample selected for this research was 317 users, to whom a questionnaire was applied to collect the necessary information. After obtaining the results, it is identified that administrative management is rated as efficient (33%); For its part, the quality of service is good with (39%). Establishing that there is a positive and significant relationship between administrative management and service quality, demonstrated by a rho correlation coefficient of 0.737 and a significance of 0.000. Regarding the dimensions, it is evident that planning a (r=0.241; p=0.000); Likewise, the organization a (r=0.745; p=0.000); for direction one (r=0.654; p=0.000); finally for the control (r=0.509; p=0.000), all of them are significantly related to the quality of the service in the Health Service Provider Institution 1 – 3 America.